Microfluidic System for Observation of Bacterial Culture and Effects on Biofilm Formation at Microscale - Zhang, Xiao-Yan (Micromachines (Basel), 2019)
Biofilms exist in the natural world and applied to many industries. However, due to the variety of characteristics caused by their complex components, biofilms can also lead to membrane fouling and recurrent infections which pose threats to human health. So, to make the best use of their advantages and avoid their disadvantages, knowing the best time and methods for improving or preventing biofilm formation is important. In situ observation without fluorescence labeling in microscale and according to a time scale is useful to research biofilm and confine its formation. In this study, we developed a microfluidic system for real-time observation of bacteria culture and biofilms development at microscale. We cultured E. coli ATCC 25922 on a chip at continuous flow of the velocity, which could promote bacterial formation. Biofilms formation under the condition of adding amoxicillin at different times is also discussed. In addition, the mixed strains from sludge were also cultured on chip, and possible factors in biofilm formation are discussed. Our results show that a microfluidic device could culture microorganisms in continuous flow and accelerate them to adhere to the surface, thereby promoting biofilm formation. Overall, this platform is a useful tool in research on initial biofilm formation, which can contribute to preventing biofouling and infections.